Protein O-GlcNAcylation as a nutrient sensor signaling placental dysfunction in hypertensive pregnancy - dos Passos Junior, Rinaldo Rodrigues; de Freitas, Raiany Alves; Dela Justina, Vanessa; San Martín, Sebastián; Lima, Victor Vitorino; Giachini, Fernanda Regina (Frontiers in Endocrinology, 2022)
The placenta is essential to the growth of a healthy baby and its function may become compromised during arterial hypertension in pregnancy. Important proteins during placentation are known to be a target for O-linked-N-acetylglucosamine (O-GlcNAc) modification and aberrant protein O-GlcNAcylation is correlated to pathological conditions, such as hypertension. We aimed to characterize how protein O-linked-N-acetylglucosamine (O-GlcNAc) impacts placental function and fetal growth throughout the pregnancy during hypertension. Spontaneously hypertensive rats (SHR) and Wistar were divided into 14, 17, and 20 days of pregnancy (DOP) groups. Rats were mated and pregnancy was confirmed by vaginal smear. On the 14th, 17th, and 20th DOP, placentas were collected and submitted to western blot, immunohistochemistry, and morphological analysis. SHR group blood pressure was higher than Wistar (p<0.001). SHR presented reduced fetal weight and increased small for gestational age fetuses on all DOP. Placental weight was increased in near-term SHR (p=0.006) whereas placental efficiency was decreased in SHR at 17 (p=0.01) and 20 DOP (p<0.0001). Morphological analysis showed reduced junctional zone area and labyrinth vasculature alterations on placentas from SHR in all DOP. O-GlcNAc protein expression was lower in placentas from SHR compared to Wistar at 14, 17, and 20 DOP. Reduced O-GlcNAc transferase (p=0.01) and O-GlcNAcase (p=0.002) enzymes expression was found on 14 DOP in SHR. Immunohistochemistry showed reduced placental O-GlcNAc content in both the junctional zone and labyrinth of the placentas from SHR. Periodic Acid-Schiff analysis showed decreased glycogen cell content in placentas from SHR at 14, 17, and 20 DOP. Moreover, glucose transporter 1 expression was found to be decreased in placentas from SHR in all DOP. Collectively, these findings suggest that reduced protein O-GlcNAcylation, resulting from decreased placental nutritional apport, contributes to placental dysfunction during hypertensive pregnancy, impairing fetal growth.